2020
DOI: 10.1080/00036846.2020.1834501
|View full text |Cite
|
Sign up to set email alerts
|

Is COVID-19 Related Anxiety an Accelerator for Responsible and Sustainable Investing ? A Sentiment Analysis

Abstract: The excessive volatility generated by the COVID-19 pandemic highlights that environmental and social issues are potential elements that businesses and governments must manage effectively and swiftly. This study seeks to test whether the rising anxiety over this pandemic has affected the attitudes and choices towards environmentally and socially responsible investing. To this end, we first use machine learning tools to examine tweets related to this unprecedented and wild shock. Second, we compare the impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 16 publications
0
25
0
1
Order By: Relevance
“…The present analysis adds to the literature on the stock market response to economic downturns (Ashraf, 2020;Nofsinger and Varma, 2014;and Wu et al, 2017), concentrating on the sustainability market and the less-explored fields of sustainable indexes and the COVID-19 pandemic (Chiappini et al, 2021;Döttling & Kim, 2020;Selmi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present analysis adds to the literature on the stock market response to economic downturns (Ashraf, 2020;Nofsinger and Varma, 2014;and Wu et al, 2017), concentrating on the sustainability market and the less-explored fields of sustainable indexes and the COVID-19 pandemic (Chiappini et al, 2021;Döttling & Kim, 2020;Selmi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Chiappini et al ( 2021 ), focusing on Europe and the USA, found that sustainable indexes were negatively affected by lockdown orders—though they did not report any statistically significant different atypical returns compared to traditional indexes. Selmi et al ( 2021 ) examined whether increased anxiety over COVID-19 affected attitudes and behaviors with respect to environmentally and socially responsible investing. Using machine learning sentiment analysis, they found that increased uncertainty and worry during the emergency period did not distract investors’ attention away from environmental and social issues, and firms that proactively engaged with responsible strategies towards environmental issues tended to be more reactive to sentiments related to the consequences of the pandemic.…”
Section: Literature and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Seperti halnya studi kasus sektor pariwisata di masa pandemi Covid-19 menjadi populer dikaji berdasarkan analisis sentimen di media sosial pada tahun 2020-2021 [146]. Dinamika interaksi antar pengguna media sosial dinilai representatif sehingga menjadi data yang penting untuk dianalisis sebagai rekomendasi pengembangan ekonomi [147], [148]. Hal ini menunjukkan bahwa ruang lingkup pembahasan atau studi kasus tentang analisis sentimen di media sosial perlu diidentifikasi dari waktu ke waktu.…”
Section: Analisis Sentimen DI Media Sosialunclassified
“…Only vague parallels can be drawn with natural disasters, as nothing comparable has ever occurred except for the 1918 influenza pandemic in the distant past. Some scholars started examining whether ESG engagement is a resiliency factor during and following the Covid crisis (Albuquerque et al., 2020 ; Ding et al., 2020 ; Selmi et al., 2021 ; Umar & Gubareva, 2021 ).…”
Section: Introductionmentioning
confidence: 99%